Site‐selective atmospheric pressure plasma‐enhanced chemical vapor deposition process for micrometric deposition of plasma‐polymerized methyl methacrylate. Issue 2 (30th September 2020) - Acharya, Kishor; Bulou, Simon; Gaulain, Thomas; Gérard, Mathieu; Choquet, Patrick
Abstract: An atmospheric pressure plasma chemical vapor deposition process designed for the site‐selective deposition of organic functional materials with a sub‐millimetric lateral resolution is presented in this study. Injecting methyl methacrylate vapor in plasma post‐discharge allowed to synthesize plasma‐polymerized methyl methacrylate (ppMMA) coatings on metallic, dielectric, and polymer substrates at close to room temperature (40°C). A circular dot, as small as 400 µm in diameter, of ppMMA is deposited and characterized by Fourier‐transform infrared spectroscopy, X‐ray photoelectron spectroscopy, and high‐resolution mass spectrometry. Oligomeric species of poly‐MMA up to n = 18 have been detected, evidencing the particularly "soft" polymerization offered by the presented process. Abstract : In‐lab developed atmospheric pressure plasma chemical vapor deposition process demonstrates its ability for site‐selected and solvent‐free deposition of plasma polymer with resolution down to 400 µm. As‐grown plasma polymer micrometric dots of methyl methacrylate evidence oligomeric species of poly‐MMA up to n = 18. Due to post‐discharge deposition, the substrate temperature is kept below 40°C, allowing coatings on stainless steel, dielectric, and polymer.